Assessing the Fiscal Burden of Overweight and Obesity in Japan through Application of a Public Economic Framework - Ataru Igarashi; Cillian Copeland; Nikos Kotsopoulos; Riku Ota; Silvia Capucci; Daisuke Adachi (Journal of Health Economics and Outcomes Research, 2024)
# Introduction Obesity continues to represent a significant public health concern, with a broad impact from both a health and economic perspective.